A semi‐explicit integration scheme for weakly‐coupled poroelasticity with nonlinear permeability. Issue 1 (25th January 2021) - Altmann, Robert; Maier, Roland; Unger, Benjamin
Abstract: Within the time integration of linear elliptic‐parabolic problems such as poroelasticity, large systems have to be solved in every time step. With a semi‐explicit approach, these systems decouple, leading to a remarkable speed‐up. This paper indicates that this idea can also be applied to nonlinear problems such as poroelasticity with nonlinear permeability. To see this, we consider a related toy problem.